2023
DOI: 10.1186/s40104-023-00905-5
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cells in farm animals: current status and future direction

Abstract: A healthy intestine plays an important role in the growth and development of farm animals. In small intestine, Paneth cells are well known for their regulation of intestinal microbiota and intestinal stem cells (ISCs). Although there has been a lot of studies and reviews on human and murine Paneth cells under intestinal homeostasis or disorders, little is known about Paneth cells in farm animals. Most farm animals possess Paneth cells in their small intestine, as identified by various staining methods, and Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 126 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…However, further investigation is necessary to determine whether Paneth cells are truly absent from cats. A previous study noted the absence of Paneth cells in cats, dogs, raccoons, and pigs (Gelberg 2014), but Paneth cells were later identified in pigs at low levels (Cui et al 2023) Feline enteroids are an important tool for studying viral and parasitic infections, but their unusually early growth arrest limits their usefulness. We showed that fibroblast feeder cells extend the lifetime of feline enteroids, especially in jejunum samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, further investigation is necessary to determine whether Paneth cells are truly absent from cats. A previous study noted the absence of Paneth cells in cats, dogs, raccoons, and pigs (Gelberg 2014), but Paneth cells were later identified in pigs at low levels (Cui et al 2023) Feline enteroids are an important tool for studying viral and parasitic infections, but their unusually early growth arrest limits their usefulness. We showed that fibroblast feeder cells extend the lifetime of feline enteroids, especially in jejunum samples.…”
Section: Discussionmentioning
confidence: 99%